Tunable diamond raman lasers for resonance photo-ionization and ion beam production - Echarri , Daniel T.; Chrysalidis , Katerina; Fedosseev , Valentin N.; Heinke , Reinhard; Marsh , Bruce A.; Reich , Bianca B.; Granados , Eduardo (Frontiers in Physics, 2022)
Lasers with wide tunability and tailored linewidth are key assets for spectroscopy research and applications. We show that diamond, when configured as a Raman laser, provides agile access to a broad range of wavelengths while being capable of efficient and selective photo-excitation of atomic species and suitable spectroscopic applications thanks to its narrow linewidth. We demonstrate the use of a compact diamond Raman laser capable of efficient ion beam production by resonance ionization of Sm isotopes in a hot metal cavity. The ionization efficiency was compared with a conventional Ti:sapphire laser operating at the same wavelength. Our results show that the overall ion current produced by the diamond Raman laser was comparable to that of the commonly used Ti:sapphire lasers. This demonstrates the photo-ionization capability of Raman lasers in the Doppler broadening-dominated regime, even with the considerable differences in their spectral properties. In order to theoretically corroborate the obtained data and with an eye on studying the most convenient spectral properties for photo-ionization experiments, we propose a simple excitation model that analyzes and compares the spectral overlap of the Raman and Ti:Sapphire lasers with the Doppler-broadened atomic spectral line. We demonstrate that Raman lasers are a suitable source for resonance photo-ionization applications in this regime.